2003
DOI: 10.1111/j.1348-0421.2003.tb03422.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Human Rotaviruses, Especially G9 Strains, in Japan from 1996 to 2000

Abstract: Human rotaviruses (HRVs) are the most important etiologic agents of severe diarrhea among infants and young children worldwide (4,16). The virus has a genome of 11 RNA segments enclosed in a capsid composed of three protein layers. The structural proteins VP1, VP2 and VP3 comprise the core layer, the group determinant protein VP6 makes up the inner capsid, and the major glycoprotein VP7 and minor proteasesensitive protein VP4 make up the outer capsid. Both VP7 and VP4, especially VP7, can induce neutralizing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
43
0
1

Year Published

2004
2004
2007
2007

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 31 publications
6
43
0
1
Order By: Relevance
“…Most novel rotaviruses may derive from reassortment between progenitor viruses from different species (23). In the present study and other phylogenetic analyses (13,27,34), several G9 lineages distinct from the major G9 lineage have been demonstrated to exist in recent human G9 strains. The VP7 genes of the Japanese porcine G9 strains discussed here were more closely related to some of these variant G9 lineages, which comprise human Japanese (K-1, 99-SP1904VP7, and 99-TK2091VP7) and Chinese (t203) G9 strains, than to the major G9 lineage.…”
supporting
confidence: 62%
“…Most novel rotaviruses may derive from reassortment between progenitor viruses from different species (23). In the present study and other phylogenetic analyses (13,27,34), several G9 lineages distinct from the major G9 lineage have been demonstrated to exist in recent human G9 strains. The VP7 genes of the Japanese porcine G9 strains discussed here were more closely related to some of these variant G9 lineages, which comprise human Japanese (K-1, 99-SP1904VP7, and 99-TK2091VP7) and Chinese (t203) G9 strains, than to the major G9 lineage.…”
supporting
confidence: 62%
“…Instead, all the G9 strains isolated during that time period in both countries have been reported to bear lineage 3 VP7. More recently, however, the reemergence of the lineage 1 G9 viruses has been reported in Japan (52). Regarding the lineage 2 G9 VP7, it has never been detected outside of India, which may suggest its distinct evolutionary lineage, different from the lineage 1 or 3 VR7.…”
Section: Discussionmentioning
confidence: 98%
“…Such studies have demonstrated the existence of at least three phylogenetic sequence lineages among the G9 rotavirus VP7 genes (2,19,25,29,30,35,40,42,43,52,53). In addition, differences in the reactivity pattern of certain G9-specific monoclonal antibodies (MAbs) against selected G9 isolates in lineages 1 to 3 were reported (6,25,39,52,53). However, a comparative systematic characterization of the VP7 neutralization specificities of G9 rotavirus strains belonging to lineage 1, 2, or 3 has not been made, which forms the aim of this study.…”
mentioning
confidence: 99%
“…Extensive epidemiological studies of rotavirus infection worldwide indicated that G1 was the most prevalent genotype (5,13,15,19,21,28,36). However, the new variants G2 and G3 emerged to become the leading genotypes in Japan from 2001 to 2004 (24,35).…”
Section: Discussionmentioning
confidence: 99%